Current and future designs for total ankle replacement. Issue 5 (September 2016) - Roukis, Thomas S.
Abstract : Total ankle replacement (TAR) longevity continues to be questioned and poorly understood, especially the effect, if any, specific design characteristics have on prosthesis survival. The commonly held belief that first generation TAR prostheses were far inferior to the second generation prostheses and that these are in turn inferior to available third and fourth generation TAR systems is not universally supported. What is clear is that as the frequency of primary TAR continues to build, revision will become more commonplace. Unfortunately, a large percentage of published literature regarding primary TAR is riddled with bias because of industry sponsorship and inventor-paid consultant involvement. Evaluation of National Joint Registry (NJR) data may provide a better understanding of reasonable outcome expectations for foot and ankle surgeons. When analyzing the data available within NJR specific to primary TAR, four usage trends exist: abandonment, minimal use, initial embracement with diminished use, and initial embracement with sustained growth. Despite 10 fixed-bearing systems and one mobile-bearing TAR system available in the United States, few have any dedicated revision components. This is a problem because currently there are no "standard principles" for revision TAR and the approaches are technically complex, fraught with complications, and no one approach represents the only answer. There is a real need for a NJR that reports on primary TAR in the United States and tracks long-term survivorship after revision TAR. Future efforts should be directed in these areas.